Prevalencia e impacto clínico de la sensibilización a látex y frutas en estudiantes de odontología de la Universidad de Antioquia y su relación con alergia a frutas (2015)
ABSTRACT: To determine the prevalence and clinical impact of sensitization to latex and to five tropical fruits (banana, avocado, kiwi, pineapple and passion fruit) in dentistry students. Methods: Analytical cross-sectional study of 128 dentistry students at University of Antioquia in Medellín, Colombia. Information was collected by means of a questionnaire and skin prick tests with latex and fruits were done. Results: All students reported having had contact with latex. Nine of them informed at least one episode of adverse reaction to contact with latex without proof of sensitization to it. Five reported at least one reaction with one of the fruits, but skin prick tests were negative. Four of the 14 students who reported gastrointestinal symptoms were sensitized to latex or to one of the tested fruits. Overall, latex sensitization rate was 3.1%. Conclusion: This percentage of sensitization to latex is lower than that in other studies; this may be due to the expression of immune mechanisms other than IgE mediation. We failed to demonstrate a higher sensitization rate to latex as students advanced in their career. The association between gastrointestinal symptoms and sensitization to both fruit and latex is to be emphasized. Keywords: Allergy, Fruits, Health care students, Hipersensitivity, Latex.